Necrotic Lesions Associated with Desomorphine ("Krokodil") Drug Abuse: a Systematic Review - Elitsa Sabeva; Dimitar Dochev (eJournal of Oral Maxillofacial Research)
Objectives: This systematic review of case reports and case series aims to identify the types of necrotic alterations caused by desomorphine ("Krokodil") and the diagnostic methods used in such cases.